Short communication. Effects of the plant growth stimulant SBPI on Bemisia tabaci Genn. (Homoptera: Aleyrodidae) - Gómez, A.A.; Alonso, D.; Nombela, G.; Muñiz, M. (Spanish Journal of Agricultural Research, 2007)
The environmentally friendly plant growth stimulant and pesticide SB Plant Invigorator (SBPI, Stan Brouard Group) helps the plant to produce quality fruit. Three days after tomato plants were sprayed for the first time with SBPI (2 mL/L solution), this product seemed to be ineffective against Bemisia tabaci adults, as the numbers of dead females were practically equal on control and treated plants. After 3 days oviposition values on control plants did not differ significantly from those on treated plants. However, 31 days after the first treatment with weekly repeated treatments, new adult whiteflies started to emerge from pupae on control plants, but no L3, L4 or new adults were found on SBPI-treated plants. However, differences in the number of 1st+2nd instar larvae were not statistically significant. From these findings it can be concluded that, under these conditions, SBPI is an effective alternative product for the control of B. tabaci on tomato plants, as foliar application inhibits larval development decreasing the risk of a new whitefly generation.